(untitled) (CIPEEX, 2022)
GENDER EQUALITY MEANS THAT MEN AND WOMEN MUST HAVE THE SAME RIGHTS AND DUTIES, AND THIS PREMISE IS CONSIDERED THE BASIS FOR BUILDING A SOCIETY FREE OF PREJUDICE AND DISCRIMINATION. THE STRUGGLE FOR GENDER EQUALITY INTENSIFIED IN THE MID-TWENTIETH CENTURY, DRIVEN MAINLY BY THE FEMINIST MOVEMENT, AND AS A CONSEQUENCE MANY RIGHTS HAVE ALREADY BEEN WON, SUCH AS WOMEN’S RIGHT TO VOTE AND ENTRY INTO THE LABOR MARKET, BUT THERE IS STILL A WAY TO DECONSTRUCT THE PREJUDICED AND STEREOTYPED VISION THAT IS EMBEDDED IN SOCIETY. JUST AS THERE IS AN IMPERATIVE TO EXTINGUISH PATRIARCHALISM SO THAT NO MAN FEELS THE RIGHT TO RAPE HIS WIFE, WHETHER SOCIALLY, ECONOMICALLY OR SEXUALLY. THROUGH THE ABOVE, IT IS INTENDED TO PRESENT AN AUDIOVISUAL PRODUCTION DEVELOPED FOR THE DISCIPLINE INTERDISCIPLINARY PROJECT OF PUBLIC HEALTH POLICIES, WITH THE ANALYSIS OF THE THEME "PRINCIPLE OF EQUALITY OF RIGHTS" IN THE LIGHT OF THE NATIONAL GUIDELINES FOR HUMAN RIGHTS EDUCATION. IN THIS SENSE, WE SOUGHT A THEORETICAL FRAMEWORK BASED ON SCIENTIFIC ARTICLES FOR THE ANALYSIS OF NEWS, VIDEOS AND IMAGES ABOUT FEMINISM AND GENDER EQUALITY. THE ANALYZED MATERIAL WAS EXPOSED IN THE AUDIOVISUAL PRODUCTION FORMAT WITH A DURATION OF APPROXIMATELY FIVE MINUTES. DIFFERENT HISTORICAL CONTEXTS BASED ON WOMEN’S STRUGGLES AND DEMANDS FOR EQUAL RIGHTS WERE OBSERVED, SUCH AS: POSITION IN THE LABOR MARKET, WITH EQUAL PAY WHEN THE SAME FUNCTION WAS PERFORMED; AND THE RIGHT TO CHOOSE THEIR REPRESENTATIVES THROUGH THE VOTE WITH FREEDOM OF EXPRESSION, AS STATED IN THE UNIVERSAL DECLARATION OF HUMAN RIGHTS. THIS WORK IS CONSIDERED TO HAVE CONTRIBUTED TO THE CLARIFICATION OF THE PRINCIPLE OF EQUAL RIGHTS AND THE AWARENESS OF BOTH MEN AND WOMEN THAT RIGHTS AND DUTIES ARE MOVING IN A TENUOUS AND HORIZONTAL LINE. EVEN TODAY THE TERM "FEMINIST" OFTEN USED IN A PEJORATIVE WAY REFERS TO VERY STRONG, VERY AGGRESSIVE, ISOLATING WOMEN, AND EVEN AGAINST MEN IN THE HEGEMONIC VIEW. MOST OF THIS COMES FROM PEOPLE WHO ARE UNAWARE OF REALITY AND DO NOT TRY TO UNDERSTAND IT. WOMEN SEEK TO OBTAIN WITH EQUALITY OF RIGHTS NOTHING MORE THAN A REMUNERATION SIMILAR TO THEIR FELLOW MEN; BEING ABLE TO MAKE DECISIONS ABOUT YOUR OWN BODY; ENGAGE IN POLITICAL REPRESENTATION AND DECISION-MAKING INHERENT IN ALL; AND SOCIALLY GET THE SAME RESPECT AS MEN. KEYWORDS: WOMEN; HUMAN RIGHTS; INEQUALITY OF RIGHTS; GENDER EQUALITY.